Texture of Being: Essays in First Philosophy - Schmitz, Kenneth L. (Studies in Philosophy and the History of Philosophy; Ser, 2007)
Intro -- Contents -- Preface -- Introduction by Paul O'Herron -- PART I. BEING -- 1. Metaphysics: Radical, Comprehensive, Determinate Discourse -- 2. Analysis by Principles and Analysis by Elements -- 3. From Anarchy to Principles: Deconstruction and the Resources of Christian Philosophy -- 4. Neither with nor without Foundations -- 5. Another Look at Objectivity -- 6. Enriching the Copula -- 7. Created Receptivity and the Philosophy of the Concrete -- 8. The Solidarity of Personalism and the Metaphysics of Existential Act -- PART II. MAN -- 9. The Geography of the Human Person -- 10. Immateriality Past and Present -- 11. The First Principle of Personal Becoming -- 12. Purity of Soul and Immortality -- 13. Is Liberalism Good Enough? -- PART III. GOD -- 14. Theological Clearances: Foreground to a Rational Recovery of God -- 15. God, Being, and Love: New Ontological Perspectives Coming from Philosophy -- 16. The Death of God and the Rebirth of Man -- 17. The Witness of Beauty: The Profi le of God -- Bibliography -- Index of Names.